Aplikasi model hidrologi Mock untuk memprediksi ketersediaan air setengah bulanan (Studi kasus di DAS Tilong dan Benain, Timor) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The research was conducted at Tilong and Benain watersheds in western of Timor island, East Nusa Tenggara. The Mock hydrologic model was applied to predict discharge of half-monthly using 15 years of hydrologic data. Four parameters of the model namely : A3 (constant of subsurface flow), A3 (constant of base flow), B2 (constant of subsurface flow recession), B3 (constant of base flow recession), were optimized using trial and error method. It was found that the optimal value of parameter for Tilong watershed were A2 = 0.256